Chronic Quadriceps Lesion with Peroneus Longus Autograft - A Case Report - Oliveira, Diego Escudeiro de; Bononi, Bruno Arjonas; Malpaga, Juliano; Vaz, Marcos; Baches, Pedro (Brazilian Journal of Case Reports, 2025)
Chronic quadriceps tendon ruptures are challenging lesions due to persistent inflammation, scarring, and tendon retraction. Although this is a disabling injury, few surgical techniques have been reported for such cases. We describe a 50-year-old Caucasian male who suddenly experienced pain in the anterior region of the knee during skating practice, with no history of direct trauma or known risk factors for associated diseases. He was treated with a modified Wave Puvertalf technique and extensor autograft reconstruction using the peroneus longus tendon.